The Effectiveness of GeoGebra-Assisted Realistic Mathematics Education in Enhancing Students’ Conceptual Understanding - Ramadhan, Farizal; Mahmudi, Ali; Nabilla, Hanif Alyaa (Department of Mathematics Education, Faculty of Teacher Training and Education, Universitas Jambi, 2025)
This research studied the application of Realistic Mathematics Education and GeoGebra which could enhance students’ conceptual understanding in mathematics, especially for geometry themes on flat-sided shapes. The study included 26 eighth-grade students of a junior public high school in Yogyakarta, Indonesia. The research, which adopted a pre-experimental design with one-group pretest–posttest arrangement, intended to explore the extent of students’ understanding improvement as GeoGebra was implemented in RME-based learning. Two conceptual understanding tests were applied, before and after intervention, alongside observation sheets aimed at monitoring activities in the class. The analysis showed that the average score increased from 47.76% to 80.29%. The test of the paired sample t-test showed a significant difference between the pre- and post-test means. Meanwhile, the N-gain score obtained 0.63, falls within a moderate category regarding effectiveness, while the learning implementation reached 98.33%, categorized as very good. These indicate that integrating RME with GeoGebra enhances accessibility in mathematics concepts to the learners and involves active participation. Limitations, however, include poor pre-knowledge of the students, irregular attendance, and distractions from using mobile phones, probably affecting their engagement and performance.